PENERAPAN SAW UNTUK MENENTUKAN PENERIMA BANTUAN PROGRAM KELUARGA HARAPAN PADA KELURAHAN RENTENG - Septia, Laili; Zaen, Mohammad Taufan Asri; Mutawalli, Lalu (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The Family Hope Program (PKH) is a social assistance program from the government which aims to improve the welfare of underprivileged people. The process for receiving aid in this program requires an effective and objective method to ensure that aid is given to those who really need it. In this study, we applied the Simple Additive Weighting (SAW) method to determine the receipt of PKH assistance in Renteng Village. The SAW method was chosen because it is able to handle multi-criteria problems in a simple but efficient way. The criteria used include pregnant women, early childhood, school / education children, disabilities and the elderly. The research results show that the SAW method can be used effectively to determine receipt of assistance by providing a ranking based on the total score of each criterion. The implementation of this method is expected to increase transparency and accuracy in the distribution of social assistance in Renteng Village. The results of the calculations show Elderly V5= 0,6815 children are more deserving of PKH assistance in Renteng Village.